“Regional Variation of Epidemiological and Microbiological Profile of Microbial Keratitis In India” - Aruna Kumari R Gupta; Roopam Kumar R Gupta (Delhi Journal of Ophthalmology)
A cross sectional study of 208 patients was done to find the regional variation of the epidemiological and microbiological profile of patients with suspected microbial keratitis. Sociodemographic data and risk factors were noted, clinically examination was done and corneal scrapings for stain and cultures were taken. Maximum patients were between the age group 41-60 years, male patients more than females. Trauma especially due to vegetative matter, in farmers residing in rural part was the most common predisposing factor. Bacterial keratitis was more than fungal keratitis with Staphylococcus aureus being the predominant bacterial and Aspergillus predominant fungal pathogen. Thus, this difference in microbial etiology for corneal ulceration in different regions of our country should be borne in mind when treating microbial keratitis.